Metakaolin-based geopolymers: Relation between formulation, physicochemical properties and efflorescence formation. (1st February 2020) - Longhi, Márlon A.; Rodríguez, Erich D.; Walkley, Brant; Zhang, Zuhua; Kirchheim, Ana Paula
Abstract: The efflorescence formation in metakaolin-based geopolymers is assessed in this study to provide a better understanding of the effect of the synthesis parameters. Efflorescence formation depends on the physical and chemical properties of geopolymers as well as the environmental exposure conditions. In this study a set of fifteen geopolymers were synthesized using different formulation. An accelerated test of efflorescence development is presented, where the grade of degradation was evaluated by visual observation and correlated to leaching potential, physical properties and microstructural features. The use of soluble silicate in the activator provides a denser and a less permeable matrix. This makes the extraction of free alkalis to the surface more difficult, reducing the extent of alkali leaching and therefore efflorescence. The use of K + is also effective to reduce visible efflorescence. The efflorescence formation is predicted by the properties of the gel formed which are dependent on the mix proportioning.